The promise of transferable fishing concessions on EU fisheries. (18th April 2017) - Kanik, Zafer; Kucuksenel, Serkan
Abstract: Two of the main proposals for the reform of the European Union (EU) Common Fisheries Policy (CFP) in 2011 were related to maximum sustainable yield (MSY) and transferable fishing concessions (TFCs). The European Commission (EC) proposed the goal of achieving MSY for all European fisheries. The EC also proposed implementation of TFCs under some major principles including reserving a part of total quotas for small‐scale fishermen in order to prevent the disappearance of small‐scale fishing communities in coastal regions. Even though TFCs have not been a major part of the last reform in 2013, we theoretically study what the potential effects of TFCs would be on the achievement process of MSY harvesting conditions under the major principles defined by the EC. We find that the level of reserved quotas for small‐scale fishermen does matter since reserving more quotas for small‐scale fishermen, using more selective fishing techniques than large‐scale fishermen, reduces the time needed to achieve MSY.